Assistance in Establishing Microenterprises for Traditional Medicine (UMOT) and Implementing The Certification Procedure for Good Manufacturing Practices for Conventional Medicines (CPOTB) in The Dasa Wisma, West Tanah Tinggi Village, Ternate City - Nur, Amran; Marwati, Eri; Tjiroso, Bambang; Fiskia, Ermalyanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The Moloku Kie Raha area in North Maluku is a remote region in the northern part of the Indonesian archipelago. It has great potential for natural resources, particularly in producing essential commodities such as cloves, nutmeg, and mace. However, a group of women from RW 4 Tanah Tinggi Barat Subdistrict needed to understand the procedures for establishing UMOT and implementing CPOTB and the necessary documentation. The goal of the community service was to assist the RW 4 Dasa Wisma Women group in Tanah Tinggi Barat Subdistrict to establish UMOT in Ternate City and fulfill the CPOTB requirements to obtain BPOM permission. The activities included socialization of UMOT establishment and CPOTB implementation, training in preparing CPOTB documents, assistance in CPOTB implementation and production layout, support with registration (e-Registration), product marketing, and overall activity evaluation. The community service, conducted with a community empowerment framework, proceeded smoothly. The implementing team assisted in establishing UMOT, training in preparing CPOTB documents, assisting in CPOTB implementation and production layouts, registration support, and creating social media and marketplace platforms. The team also assisted with production equipment to meet the required standards, facilitating the Dasa Wisma RW 04 Women's Group business in Tanah Tinggi Barat Sub-district. The service team addressed mothers' economic productivity issues, offering solutions to the Dasa Wisma RW 04 women's group. With the establishment of UMOT for essential oils production, the group can increase economic income through a cost-effective manufacturing process, ultimately boosting their profits.